(untitled) (Journal of Industrial and Mechanical Engineering, 2019)
Duplex stainless steels offer an attractive combination of mechanical strength and corrosion resistance (used in the petrochemical industry). With modern welding processes in pulsed transfer mode (GMAW-P) or with double pulse (GMAW-PP) a more precise control of metal transfer is obtained with lower average current values and consequently a lower heat input, generating less distortion and less microstructural damage to the base materials, compared with the conventional semiautomatic welding process (GMAW). The objective of this work was to study the effect of the pulsed arc and the double pulse on the geometric characteristics of the bead, the dilution with the base material, the microstructural evolution and the hardness with a super duplex stainless steel consumable. In particular, the selection of pulse parameters that generate an adequate bead geometry to be used as a root pass was sought.